Decolonization of Feminism in the Malayan Nationalist Movement: A Case Study of Ibu Zain and Shamsiah Fakeh - Jamil, Asyiqah Binti Mohamad; Abdullah, Asilatul Hanaa Binti (Universitas Islam Internasional Indonesia (UIII), 2022)
The misrepresentation of Southeast Asians throughout history was often the results of the White Man’s burden doctrine practiced by Western colonialists, which clouded their perceptions of Southeast Asians, resulting in claims that Southeast Asians were inferior. This Eurocentric idea has distorted the representation of colonized nations in general. However, the worst Eurocentric fallacy is regarding Muslim women in Southeast Asia. They were not only misrepresented but also intimidated by the patriarchal nature of orientalism. Muslim women were, and indeed often still are, viewed as vulnerable victims that need to be saved from their men, making them quarry of double oppression. The most unfortunate part is even many modern white feminists still subscribe to these Eurocentric ideas. Thus, this paper aims to decolonize this narrative by illustrating the history of women’s involvement in politics from the time of the Malay Sultanate until post-World War II Malaya. This research also explores women’s participation in the far-right and far-left political movements in Malaya, with special references to Ibu Zain and Shamsiah Fakeh. We demonstrate the independence of Malayan women and affirm that they were well-presented in Malayan politics over this period of time.